The The gender perspective in Law. Some reflections by the light of the judgment of the Inter-American Court of human rights of November 18, 2022 (Angulo Losada vs. Bolivia case) - Santos Pérez , M. Lourdes (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Based on the Judgment of the Inter-American Court of Human Rights in the case of Angulo Losada vs. Bolivia, we propose a reflection on the meaning of the gender perspective in law. Although this approach is not new in the jurisprudence of the Court, we will argue that the Judgment constitutes a turning point in its consolidation within the Inter-American Human Rights System. A review of the arguments used by the Court in previous cases in which it applied the gender perspective leads to the conclusion that the main novelty lies in the reparation measures agreed upon, which seek to have not only a restitutive effect but also, and mainly, a corrective effect to remedy what is referred to as a situation of structural discrimination against women.
Keywords: Inter-American Court of Human Rights; Angulo Losada v. Bolivia case; gender perspective in Law